Data for: Effect of nutrition on growth and virulence of Beauveria bassiana s.l. against the planthopper Delphacodes kuscheli - Toledo, Andrea Vanesa (2021)
The effect of different culture media on growth and virulence of Beauveria bassiana s.l. (Balsamo-Crivelli) Vuillemin (Hypocreales: Cordycipitaceae) BbCEP147 against Delphacodes kuscheli Fennah (Hemiptera: Delphacidae) was evaluated with the aim to select some nutritional sources to incorporate them in future mass production studies. Ten agar-agar 2% media were used. Media were supplemented with 10 g of sucrose and 4 % flour of amaranth or chia or flax or oat bran or parboiled rice or poppy or quinoa or wheat germ. Sabouraud’s dextrose agar with 1 % yeast extract (SDAY) was used as control, while sucrose agar medium supplemented with 2 % chitin was used as possible inductor of enzymatic activity. Colony growth, conidial yield, size, viability, adherence, hydrophobicity, protease activity, cumulative mortality and median survival time (MST) were determined. Our results indicated that all virulence parameters measured were influenced by nutritional source. The highest percentages of D. kuscheli mortality (equal or higher than 90%) were recorded on media supplemented with amaranth, chia and chitin, although no significant differences were observed respect to the control medium (85 %). In addition, the lowest MST values were recorded on medium supplemented with chia (5.17 days). Media supplemented with chitin or chia, in which conidia showed high ability of adherence and hydrophobicity, were associated with high D. kuscheli cumulative mortality. Likewise, cumulative mortality, conidial viability, hydrophobicity and adherence together explained the maximal amount of total variance indicating that these variables can be used as indicators of B. bassiana CEP147 virulence against D. kuscheli. In summary, our results indicate that amaranth and chia flour, which are rich in proteins, minerals and vitamins, have desirable attributes to be incorporated in future studies of fungal mass production with the propose to increase conidial performance and virulence.